Study on Labeling of Tc-99m with L-Aspartic Acid - Kang, Sung-A; Park, Yeong-Jae (Asian Journal of Chemistry, 2014)
A L-aspartic acid was used as a chelating ligand for labeling Tc-99m. Labeling experiments of Tc-99m with L-aspartic acid were carried out at varying temperature, time, pH and concentration ratio of L-aspartic acid to SnCl2. For the effects of temperature (25, 40, 60 and 80 ºC) and pH (2, 6-7, 10) on the labeling, the best results were obtained at 80 ºC and in the neutral pH range, respectively. For the effect of concentration ratio of L-aspartic acid to SnCl2 (15, 30, 45, 80 and 100), the best one was obtained at 45. The labeling of Tc-99m was investigated by radio-ITLC using methyl ethyl ketone and 0.9 % saline solution as solvents. The method to determine percentages of Tc species formed at given reaction conditions was described. The best result for the labeling was obtained at 80 ºC in the neutral pH range with the concentration ratio of aspartic acid to SnCl2 of 45. At those conditions, the extent of labeling reached 90 % for 1 h and 95 % for 90 min.